Development of innovation through the integration of startup-projects - Ровинская, Настасья Юрьевна (Technology audit and production reserves, 2016)
The problem of innovation development was studied in this article. This problem is actual because the level of maturity of innovation is directly proportional to the level of economics development. Global Innovation Index confirms this fact. The elements of startup-ecosystem were studied based on the experience of state Israel in the hi-tech area. The life cycle of startup-projects was shown. The statistic information about quantity of startups in Israel with index of success has been researched. The areas of investment have been allotted. The comparative analysis of investments volume in innovation activities of Israel and Ukraine has been performed. Information of Ukraine accelerators/incubators, R&D and scientists, the laws of innovation activities were considered. Also there were described stages of financing of startup-projects. Factors, which influence negatively on the level of hi-tech development, were determined in research. The model of support for development of innovation has been proposed that emend these determined factors. The results can be adopted for acceleration of hi-tech projects on the existing production facilities.